New species of the genus Glyphobythus Raffray, 1904 (Coleoptera: Staphylinidae: Pselaphinae) from Turkey - Hlaváč, Peter; Brachat, Volker (Zootaxa, 2015)
A new species of the tribe Bythinini, Glyphobythus anatolicus Hlaváč & Brachat sp. nov. from the province Zonguldak, Turkey is described.